Particle Motion around Charged Black Holes in Generalized Dilaton-Axion Gravity. (16th September 2018) - Sarkar, Susmita; Rahaman, Farook; Radinschi, Irina; Grammenos, Theophanes; Chakraborty, Joydeep
Abstract : The behaviour of massive and massless test particles around asymptotically flat and spherically symmetric, charged black holes in the context of generalized dilaton-axion gravity in four dimensions is studied. All the possible motions are investigated by calculating and plotting the corresponding effective potential for the massless and massive particles as well. Further, the motion of massive (charged or uncharged) test particles in the gravitational field of charged black holes in generalized dilaton-axion gravity for the cases of static and nonstatic equilibrium is investigated by applying the Hamilton-Jacobi approach.